Terrestrial free space optical communications in Bangladesh: transmission channel characterization - Kazi Shahiduzzaman; Majumder F. Haider; Bijoy K. Karmaker (International Journal of Electrical and Computer Engineering (IJECE), 2019)
This research work focused on transmission channel characterization of Free-Space-Optical (FSO) communications technology for deploying in the developing country like Bangladesh. To meet the tremendous amount of data traffic, mobile operators and ISPs need better solution than the existing RF and fiber optic communications. Moreover, Bangladesh is entering in the era of satellite communications by launching its own satellite.  So, Bangladesh needs such communication technology that provides higher channel bandwidth, sophisticated transmission security and can cope channel dispersion. FSO is a good candidate that can meet all these features. The transmission channel characterization plays a significant role in optimizing the performance of FSO link.  In this work, the channel characterization of FSO technology from the weather perspective of Bangladesh has been investigated thoroughly. The obtained results show that the atmospheric scattering effect does not hamper the short range FSO link performance, whereas, the atmospheric turbulence effect is not favorable to deploy FSO technology with reasonable quality signal unless it is optimized properly using antenna aperture averaging technique.